Review of Greek Month in London, November 1975, Recordings of Contemporary Greek Music: Greek Composers 2nd Series, Greek Electronic Music, Vol. 1, and Jani Christou, Vol. 1 - Jones, David (Contact: A Journal for Contemporary Music (1971-1990), 1976)